Who wins the 2008 Ghana presidential elections? GIS options and lessons from exploring the 2000 and 2004 voting patterns in the Greater Accra Region - Kufogbe, S.K.; Jayson-Quashigah, P-N.; Yiran, G.B. (Faculty of Social Science, University of Ghana, 2010)
This study used GIS as an analytical tool to study the voting outcomes of the 2000 and 2004 presidential elections in the Greater Accra Region. It shows the patterns that have occurred among the constituencies over the two voting periods between the two major parties, the National Democratic Congress (NDC) and the New Patriotic Party (NPP). The analysis shows that at both elections, the more rural areas were claimed by the socialist NDC party while the more urban areas were won by the capitalist NPP. The study further revealed the socio-economic cleavages such as income, education and ethnicity that exist between the two parties in the region. From the three constituencies sampled, it was obvious that factors influencing voting patterns varied across space. While in Ada and Ningo-Prapram, party voted was based on affiliation, in Tema West, it was more on other issues such as party policies and qualities of the leader than affiliation. Using GIS mapping tools, strongholds of both parties as well as swing zones which are very strategic for election campaigns were determined
Keywords: National Democratic Congress, New Patriotic Party, Voting patterns, GIS